Ultramafic to mafic granulites from the Larsemann Hills, East Antarctica: Geochemistry and tectonic implications. (1st September 2017) - Tong, Laixi; Jahn, Bor-ming; Liu, Xiaohan; Liang, Xirong; Xu, Yi-gang; Ionov, Dmitri
Graphical abstract: Highlights: Ultramafic to mafic granulites in the Larsemann Hills of East Antarctica show composition features of igneous cumulate. Their peak granulite facies recrystallization condition is 860–900 °C. Their negative Nb and Ti anomalies suggest they were formed in a subduction zone related to arc-continent collision. Peak granulite metamorphism and arc-continent collision occurred in the early Neoproterozoic (990–900 Ma) Rayner orogeny. Abstract: The Larsemann Hills area is part of a reworked early Neoproterozoic metamorphic terrain in southwestern Prydz Bay, East Antarctica. Ultramafic and mafic granulites, whose origins remain controversial, occur as lenses, boudins or layered bodies within the para- and ortho-gneiss in the region. The ultramafic and mafic granulites show spinel-olivine-bearing and two-pyroxene-bearing mineral assemblages recrystallized at 860–900 °C. Their bulk rock analyses indicate an origin as igneous cumulates, with high Mg # (molar MgO/(MgO + FeO)) from 0.73 to 0.84 for ultramafic granulite and from 0.46 to 0.78 for mostly mafic granulite as well as high Cr and Ni contents ([Cr] and [Ni] up to 1826 ppm and 1400 ppm respectively for ultramafic granulite and [Cr] of 1460 ppm for mafic granulite). Trace element patterns show pronounced negative Nb anomalies, suggesting a subduction-related tectonic setting for their precursors, consistent with derivation from arc basalts, also suggested by low TiO2 and K-enrichment in mafic granulites. The ultramafic to mafic granulites may have been formed in a subduction-related continental back-arc basin environment simultaneously with peak metamorphism associated with arc-continent collision during the early Neoproterozoic (990–900 Ma) Rayner orogeny.